Analisis Unsur Cuaca terhadap Variabilitas Musiman di Bandara Internasional I Gusti Ngurah Rai (2020-2024) - Widyandaru, Karmelita Asri; Wulaning Sari, Ni Made Orcidia; Haryanto, Yosafat Donni (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2025)
This study was conducted to identify the characteristics and variability of weather elements at I Gusti Ngurah Rai International Airport, Bali, based on data from 2020 to 2024. The aim of this research is to analyze the relationship between weather variability and seasonal patterns, including visibility, temperature, cloud base height, wind direction, and precipitation. The method used is descriptive quantitative analysis, involving the processing of secondary data from Aerodrome Climatological Summary (ACS) and Precipitation (CH) reports. The data is analyzed on a monthly basis and categorized according to monsoon seasons (wet, dry, and two transition periods). The results show that visibility is dominated by the <8000 m category, with the highest percentage occurring during the wet season and the lowest during the dry season. The 25–30°C temperature range occurs more frequently during the dry season, while winds predominantly come from the northwest sector during the wet season and shift to the east during the dry season.